Influences of hardening agent on some physical and mechanical properties of medium-density fiberboard - Osman Çamlıbel; Murat Aydın (Turkish Journal of Forestry, 2022)
Effects of Ammonium chloride (NH4CI) as a hardening agent on thickness swelling (TS), water absorption (WA), screw holding resistance (SHR), Janka hardness, modulus of rupture (MOR), modulus of elasticity (MOE), and internal bonding (IB) properties of medium-density fiberboard (MDF) were evaluated. Target densities were 712 and 715 kg/m³ for hardener applied (0.75 kg/m³ solid as 10% solution (fiber dry wt.)) and unmodified factory made 18 mm thick MDF, respectively. A total of 400 samples were tested. Boards produced without hardener presented better mechanical properties except for SHR. Indeed, SHR was around 9.2% improved by hardener utilization. However, hardener utilization caused around 8.4%, 7.3%, 3.6%, and 1.3% decreases for MOE, MOR, IB, and Janka hardness, respectively. Surprisingly, soaking time caused opposite results for TS and WA. The TS and WA of the hardener utilized MDF decreased around 40.3% and 29.6% for short-term soaking (2h) but remarkable increases (around 62.4% and 20%, respectively) were observed for long-term (24h) soaking. Statistical analysis proved that there were statistically significant (P<0.05) differences between all the evaluated properties.